2004
DOI: 10.1161/01.cir.0000109701.77059.e9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glutathione Peroxidase Prevents Left Ventricular Remodeling and Failure After Myocardial Infarction in Mice

Abstract: Background-Oxidative stress plays an important role in the pathophysiology of heart failure. We determined whether the overexpression of glutathione peroxidase (GSHPx) could attenuate left ventricular (LV) remodeling and failure after myocardial infarction (MI). Methods and Results-We created MI in 12-to 16-week-old, male GSHPx transgenic mice (TGϩMI) and nontransgenic wild-type littermates (WTϩMI) by ligating the left coronary artery. GSHPx activity was increased in the hearts of TG mice, with no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
176
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(194 citation statements)
references
References 34 publications
11
176
1
6
Order By: Relevance
“…After 8 wk of injection, echocardiographic studies were performed under light anesthesia with tribromoethanol-amylene hydrate (Avertin; 2.5% wt/ vol, 8 l/g ip) and spontaneous respiration. Two-dimensional targeted M-mode tracings were recorded at a paper speed of 50 mm/s (28).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After 8 wk of injection, echocardiographic studies were performed under light anesthesia with tribromoethanol-amylene hydrate (Avertin; 2.5% wt/ vol, 8 l/g ip) and spontaneous respiration. Two-dimensional targeted M-mode tracings were recorded at a paper speed of 50 mm/s (28).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have demonstrated that H 2 O 2 and hydroxyl radical (⅐OH), generated via superoxide anion (O 2 Ϫ ⅐), play an important role in the development and progression of myocardial remodeling in the pacing-induced heart failure as well as in the postinfarct heart failure model (10,28). Furthermore, in vitro studies demonstrated that ROS could directly induce hypertrophy and apoptosis in cardiac myocytes (30).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that anti-oxidant treatment reduces infarct size in the rat AMI model (Hung et al 2002;Sahna et al 2002). The acute release of large amounts of ROS is directly related to cell death associated with AMI, whereas the chronic release of ROS may be associated with the development of left ventricular hypertrophy and HF (Sorescu and Griendling 2002;Shiomi et al 2004). Anti-oxidant treatment appears to reduce cardiac fibrosis (Sia et al 2002).…”
Section: Discussionmentioning
confidence: 99%